When helping hurts : how to alleviate poverty without hurting the poor-- and yourself - Corbett, Steve; Fikkert, Brian (Chicago, IL : Moody Publishers, 2012)
Churches and individual Christians typically have faulty assumptions about the causes of poverty, resulting in the use of strategies that do considerable harm to poor people and themselves. When Helping Hurts provides foundational concepts, clearly articulated general principles and relevant applications. The result is an effective and holistic ministry to the poor, not a truncated gospel. A situation is assessed for whether relief, rehabilitation, or development is the best response to a situation. Efforts are characterized by an "asset based" approach rather than a "needs based" approach. Short term mission efforts are addressed and microenterprise development (MED) is explored. --from publisher description.
Foundational concepts for helping without hurting -- Why did Jesus come to earth? -- What's the problem? -- Are we there yet? -- General principles for helping without hurting -- Not all poverty is created equal -- Give me your tired, your poor, and their assets -- McDevelopment : over 2.5 billion people not served -- Practical strategies for helping without hurting -- Doing short-term missions without doing long-term harm -- Yes, in your backyard -- And to the ends of the earth -- Getting started on helping without hurting -- Excuse me, can you spare some change? -- On your mark, get set, go -- A final word : the most important step.
Edition statement taken from upper right corner of front cover.
"Foreword by David Platt"--Cover.
Includes bibliographical references.
Keywords: Church work with the poor; Poverty -- Religious aspects -- Christianity